Front Cover: Modulation and Visualization of EF‐G Power Stroke During Ribosomal Translocation (ChemBioChem 23/2019). (8th November 2019) - Yin, Heng; Gavriliuc, Miriam; Lin, Ran; Xu, Shoujun; Wang, Yuhong
Abstract : Power to the finish line : During ribosomal translocation, elongation factor G (EF‐G) produces a significant power stroke that is the main driving force for the ribosome to move forward one codon at a time (top kangaroo). The force is generated through a large change in conformation (green, ribosome large subunit; red, EF‐G). Consequently, when a crosslinker is implemented, only a weak power stroke is generated (bottom kangaroo). Interestingly, the ribosome still moves by one codon at a time, but at a slower rate. More information can be found in the full paper by S. Xu, Y. Wang, et al. on page 2927 in Issue 23, 2019 (DOI: 10.1002/cbic.201900276 ).